Track-before-detect in distributed sensor applications - Rong Yang (EURASIP Journal on Advances in Signal Processing, 2011)
Abstract In this article, we propose a new extension to a Dynamic Programming Algorithm (DPA) approach for Track-before-Detect challenges. This extension enables the DPA to process time-delayed sensor data directly. Such delay might appear because of delays in communication networks. The extended DPA is identical to the recursive standard DPA in case of all sensor data appear in the timely correct order. Furthermore, an intense evaluation of the Accumulated State Density (ASD) filter is given on simulation data. Last but not least, we apply a combination of DPA and ASD on data of a real radar system and present the resulting tracks. Our experience concerning this combination is a seamless cooperation between the track initialization by DPA and a track maintenance by ASD filter.